Implementation Of Marketing Communication Strategy To Overcome Business Reputation Challenges: A Case Study On PPM Management - Nabilla Rahmadhanni Firdaus; Albari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the implementation of marketing communication strategies carried out by PPM Manajemen to overcome business reputation resistance in the digital and globalization era. This study uses a qualitative approach with descriptive methods, utilizing in-depth interviews, direct observation, and document analysis as data collection techniques. The unit of analysis in this study involves marketing managers, marketing supervisors, and social media specialists who have strategic roles in marketing communications. The results of the study indicate that the adaptive use of digital technology and social media can increase the effectiveness of marketing communications and improve business reputations that have been negatively impacted. The implications of this study emphasize the importance of social media-based data analysis, consistent communication implementation, and strengthening crisis communication protocols to maintain the company's reputation and increase audience engagement.